Trypanosomiasis risk and innovation : the case of livestock farmers in West Africa - (:unkn) unknown (My University, 2015)
African animal trypanosomosis, transmitted by tsetse flies, are among the main animal health constraints to the development and intensification of cattle production in sub-Saharan Africa. Their control relies on two major strategies: the farmer-based control aiming at controlling the disease in order to allow a cost-effective production, and the centralized state intervention mostly targeting the eradication of the vector and the disease. This second strategy recently spread in the framework of the Pan African Tsetse and Trypanosomosis Eradication Campaign (PATTEC), coordinated by the African Union. I aimed to characterize the innovation capacities of livestock producers facing this animal health risk and vice versa the effect of risk control on innovation trajectories of livestock farmers. The study area concerned two west african countries: Burkina Faso and Senegal. In Senegal, we developed an original cost-benefit approach of the eradication program, and showed that the expected benefits mainly relie on innovation, thanks to the productivity benefits resulting from the shift from livestock breeding systems using the trypanotolerant Djakoré breed toward improved livestock breeding systems using more productive trypanosensible cattle breeds. In Burkina Faso (Mouhoun basin), the goals were to characterize the risk assessment by livestock producers, farmer-based control strategies and their capacities to adopt a new control method against tsetse flies, the insecticide footbath. At last, in order to understand and predict the impact of the evolution of the trypanosomosis risk on innovation trajectories of livestock producers and to improve the economic analysis of the eradication campaign in Senegal, a cross-sectional analysis of 10 case studies allowed identifying and characterizing the local dynamics of innovation, the rationales for action and the indicators of innovation capacities of the different groups of livestock producers. In the two study ar
Keywords: African Research